2003
DOI: 10.1152/ajpcell.00015.2003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of adherens junctions and epithelial paracellular permeability: a novel function for polyamines

Abstract: Maintenance of intestinal mucosal epithelial integrity requires polyamines that are involved in the multiple signaling pathways controlling gene expression and different epithelial cell functions. Integrity of the intestinal epithelial barrier depends on a complex of proteins composing different intercellular junctions, including tight junctions, adherens junctions, and desmosomes. E-cadherin is primarily found at the adherens junctions and plays a critical role in cell-cell adhesions that are fundamental to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 66 publications
7
109
0
Order By: Relevance
“…Experiments in cell culture showed that the effects of the ODC inhibitor could be rescued by exogenous putrescine, supporting the interpretation that these genes are regulated by polyamine-dependent mechanisms. Other groups have observed similar effects of DFMO on cell-junction proteins 51,52 , although alterations seem to be cell-type specific.…”
Section: Box 1 | Polyamines In Normal Growth Development and Tissue mentioning
confidence: 56%
“…Experiments in cell culture showed that the effects of the ODC inhibitor could be rescued by exogenous putrescine, supporting the interpretation that these genes are regulated by polyamine-dependent mechanisms. Other groups have observed similar effects of DFMO on cell-junction proteins 51,52 , although alterations seem to be cell-type specific.…”
Section: Box 1 | Polyamines In Normal Growth Development and Tissue mentioning
confidence: 56%
“…14 Previous studies have demonstrated that adherens junctions stabilization was sufficient to strengthen epithelial barrier function. 35 Our findings using electric cell-substrate impedance sensing (ECIS) suggest that the loss of TER is reduced, but we cannot rule out that this effect on TER may be influenced by Epac-mediated cell spreading affecting the intercellular space in an adhesion-independent fashion. Here we demonstrated that hypoxia-induced loss of focal adhesions is reduced by activation of Epac using paxillin as a functional marker ( Figure 5).…”
Section: Discussionmentioning
confidence: 84%
“…Nonetheless, these findings fail to explain the necessity of the coexisting TJs and AJs at the BTB that maintains its integrity during spermatogenesis. In two recent studies, it was shown that AJ disruption in the seminiferous epithelium induced by a suppression of intratesticular androgen (14) or by means of treatment of rats with Adjudin (12) did not disrupt the TJ barrier, unlike all other epithelia, where a disruption of AJ can lead to TJ barrier damage (15,16). These findings indicate that a mechanism is in place at the BTB that permits AJ restructuring while maintaining TJ integrity.…”
mentioning
confidence: 94%